Assessment of Age Category and other Factors of Contraception Acceptance among Post-Abortion Patients - Sadiq Jan, Farzana Burki, Nosheen Wahab Salman, Anila Mahmood, Ayesha Naeem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Women who have had abortions are almost immediately pregnant-risk, low post-abortion family planning usage perceived to be one of the primary and significant factors that cause of induced abortion and spontaneous abortion. The aim of the study was to determine the factors in which the women accept post-abortion contraceptive methods among abortion care service patients in our hospital. Study Design: It was a cross-sectional study conducted in the Obstetrics and Gynecology Department of Riphah International hospital, Islamabad, for six month duration from March 2022 to August 2022. Methods: 125 out of 150 participant (abortion clients) selected by sampling technique were interviewed in Mayo hospital, Lahore. We analyzed dependent and independent variables. Data analysis was done statistically by SPSS 20 version. Results: This study included 150 participants who had a first trimester abortion between the study periods, 25 participants in this study were not willing to participate in the study, ultimately the responding rate of 83%. Among the 125 participants 92% were within the age group 21-39. The maximum participants were Muslim 92% and 8% non-Muslim. The maximum participants were married 96% and 4% unmarried. Most of the participants had only received the educational status 76%. This study indicate the strong relationship between women age 21-39 with the high usage of post-abortion contraceptive 92% as compared to >40 years. The participants in our study were used 85% contraceptive method. Conclusion: Our finding shows that providing appropriate medical advice and contraceptive counseling services can increase contraceptive acceptance. Keywords: Post-abortion contraceptive, family planning, contraceptive counseling services.